On the diversity and richness of understory bryophytes at Nectandra Cloud Forest Reserve, Costa Rica - Norris, Daniel H (Biodivers Data J, 2017)
Abstract. BACKGROUND: A survey of the understory bryophytes in the Nectandra Cloud Forest Preserve yielded 1083 specimens distributed among 55 families, represented by 74 genera of mosses, 75 genera of liverworts and 3 of hornworts. We studied and analyzed the bryophytic distribution on six types of substrates: 1) corticolous, 2) epiphyllous, 3) saxicolous, 4) terricolous, 5) aquatic and 6) lignicolous. The richness and composition of bryophyte genera are compared to those of other previous bryophyte surveys from 4 other sites with different oceanic exposures, climatic and geographic conditions in Costa Rica. NEW INFORMATION: This is a report of the first extensive general survey of bryophytes at the Nectandra Reserve, a premontane cloud forest located on the Atlantic slope of Costa Rica, an area much less studied compared to the Monteverde cloud forest on the Pacific slope.